TATANAN KEHIDUPAN BARU DI ERA ADAPTASI KEBIASAAN BARU OLEH PELAKU PARIWISATA PADA MASYARAKAT KELOMPOK SADAR WISATA DI DESA WISATA MUNGGU MENGWI, BADUNG, BALI - I Ketut Murdana (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
The research in general aimed at studying or analyzing a case study of the implementation of new normal life at the new habit adaptation by tourism practitioners of tourism care group at Munggu Tourism Village, Mengwi, Badung, Bali. The primary research data are directly collected from the case study of research informan/responden who are the tourism business staff during the interview process and also from the research questionnaires. The informan/respondens were selected using purposive, snowball and abundant sampling techniques with the total numbers of 50 samples are analysed. The research revealed that based on the structured interviews 4 questions were answered by “NO” or “NOT YET” which are the cases agains the new normal, whereas based on the questionnaire 6 questions were answered by “NOT” by 35 informan/respondens of the amount of 18% were also the cases related to the new normal.